Hubungan Pengetahuan Dan Sikap Remaja Tentang Pola Makan Seimbang Dengan Tindakan Pencegahan Diabetes Mellitus Tipe 2 - Nirmalasari, Novita; Supriatin, Rahayu Dwi (Indonesian Journal of Health Community, 2025)
Diabetes mellitus is generally suffered by the elderly age group, but currently diabetes mellitus can also occur in adolescence. The main cause of type 2 diabetes mellitus in adolescents is an unbalanced lifestyle, including an unbalanced diet. The study aimed to find out the relationship between adolescents knowledge and attitudes about a balanced diet and preventive measures for type 2 diabetes mellitus at senior high school 10 Yogyakarta. The research design uses a quantitative method with proportionate stratified random sampling technique. The sample of this study was 93 respondents. The data were analyzed univariate and bivariate using Kendal's tau-b Test. The results were obtained between adolescents knowledge about diet with preventive measures for type 2 diabetes mellitus with a p-value of 0.010 (p?0.05) with a positive correlation of r=0.264 (0.2-0.399) and results between adolescents' attitudes about diet with preventive measures for type 2 diabetes mellitus with a p-value of 0.013 (p?0.05) with a positive correlation of r=0.300 (0.2-0.399). Interventions for preventing diabetes mellitus can be carried out, especially healthy living behavior. Future research can examine other factors, such as physical activity.